The role of solidarity in achieving social justice from the perspective of the Qur’an and the hadiths - Ali Shamran Rahi; Dr. Said K.Baqri; Dr. Mohammad Shirin Kar Movahed (Journal of College of Education, 2025)
Solidarity in Islam is an innate system that derives its existence from the laws of God that link human nature with the laws of the universe. A parent’s sponsorship of his children is an innate matter that a person is driven to by an innate impulse. The same applies to sponsoring his family, or his mother and father. If we seek the truth, we find in a person a desire to sponsor a poor neighbor or a poor relative who is far away from his home, or to sponsor an orphan, so he takes care of him as he takes care of his own children. This solidarity also includes society, so that fraternal ties are strengthened among its members.